Factors Associated with the Quality of Drinking Water in the Commune of Adjarra in Benin, 2014 - OUENDO, EDGARD-MARIUS DONA; DEGBEY, CYRIAQUE C.; AMADOU, A. RAMANOU (My University, 2015)
Water is a vital element to the life of living things, especially to that of human being. Its use for food and body hygiene purposes requires that it meets the norms of physicochemical and microbiological quality recommended by the World Health Organization. The aim of this work was to study the factors associated with the quality of drinking water in the commune of Adjarra in Benin in 2014. It was a descriptive and analytical cross-sectional study of the factors associated with the quality of drinking water in the commune of Adjarra in 2014. The population studied is made of two targets which are the primary targets (drinking water) and the secondary targets (the heads of households or their representative, hygiene and sanitation officials of the health center and the commune, the official of SONEB, the women’s groups and the chiefs of villages). The non-probabilistic method and techniques of reasoned choice and comprehensiveness were used respectively for hygiene and sanitation officials of the health center, of the commune, the official of the National Water Company of Benin, the women’s groups, the chiefs of villages and the six districts of the commune of Adjarra. The bacteriological analysis reveals that 9 out of 10 waters collected at the level of the supplying sources and 87.76% at the level of the storage containers are contaminated. The germs indicating pollution identified are fecal coliforms, Escherichia coli and ordinary germs. Autonomous and private wells and water points show a high degree of fecal coliforms and Escherichia coli. The study highlighted the link between the ownership status of the container used to fetch water and the quality of the drinking water (p = 0.045). The risk of contaminating the water is 7.32 times higher among households that use a dirty container to fetch water than among those who use a clean container. The factors associated with the quality of drinking water are the hygiene status of the water container and the type of water supplying source. Solving this problem requires a good communication to change the behavior of the community and a reinforcement of the drinking water supply infrastructure.
Keywords: Drinking Water; Bacteria; Contamination Index; Drinking Water Supply; Communication to Change Behavior; Benin